PERTANGGUNGJAWABAN PIDANA KURATOR BERDASARKAN PRINSIP INDEPENDENSI MENURUT HUKUM KEPAILITAN - Astiti, Sriti Hesti (Jurnal Hukum dan Peradilan, 2016)
This article aimed to criticize the juridical basis of the scope of crime mentioned on Law Number 37 of 2004, focuses on the criminal responsibility of a Curator based on independence principle of Bankruptcy Law. Essentially, bankruptcy is a part of Civil Law. However, some bankruptcy cases eventually evolve into criminal matters when a Bankruptcy Curator who is responsible for handling and administering bankruptcy case is positioned as Defendant charged with conducting criminal acts. As stated in Article 234 verse (2) of Law Number 37 of 2004, a Curator who is proven not independent during bankruptcy court may be charged with Criminal Law.Keywords: Curator, Bankruptcy, Principle of Independency, Criminal Responsibility